Evaluating Gender Differences In The Complaint Behavior Of Malaysian Consumers - Oly Ndubisi, Nelson; Tam, Yin Ling @ Adeline (Asian Academy of Management (AAM), 2007)
The aim of this paper is to investigate whether male and female Malaysian consumers differ in their dissatisfaction complaint behavior and its aftermath. The study examines the moderation effect of gender in the relationship between public complaint behavior, private complaint behavior and customer defection. Data for the study was collected from 218 randomly selected customers of retail banks in Malaysia. The results show that public and private complaints are significantly associated with defection. These findings are generic across sex-type. Theoretical and managerial implications of the findings are discussed.